Pemberdayaan Masyarakat Petani Salak dalam Pemasaran Usaha Sebagai Produk Unggulan di Kampung Banjar Seminai Kecamatan Dayun Kabupaten Siak - Andrikasmi, Sukamarriko; Firdaus, Emilda; Mubarak, Mubarak; Fitiansyah, Aidil; Haiqal, Muhammad Rafi (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2024)
The salak business community is struggling with marketing due to a lack of awareness about salak plantations in Banjar Seminai and skepticism regarding the existence of pondoh salak in Dayun Siak Riau. A potential solution is to empower the community during the harvest season by processing the abundant snake fruit into products like chips, diamonds, dodol, jenang, syrup, bakpia, candied fruit, and other innovative foods. The initiative aims to empower the salak farming community in Banjar Seminai Village, Siak Regency, by enhancing their marketing skills for salak products. This includes training and mentoring in manual and online marketing, packaging, and branding. The participatory approach engages farmers at every stage, resulting in improved knowledge and skills in marketing salak products and increased income. This empowerment aims to promote salak products from Banjar Seminai Village and positively impact the local economy.